(untitled) (Jurnal Bina Praja, 2022)
The scheme for the disbursement of social assistance through the Family Hope Program (PKH) during the COVID-19 pandemic changed, originally once every three months; now, it is carried out every month from April to December 2020. This change in the scheme has resulted in various responses from Beneficiary Families (KPM). PKH. This research is a qualitative descriptive study. Data collection in this study was conducted through in-depth interviews and direct observation in the field. In order to determine the informants, this study uses a sampling technique with purposive sampling. The results showed that the response of KPM PKH in Nagari Gunung Rajo in terms of perception, attitude, and participation aspects showed a positive response. This can be seen from the PKH KPM. They have understood the purpose of changing the PKH program assistance scheme, the terms, methods, and timing of aid distribution, and are actively participating in PKH activities. Researchers recommend the government consider changing the PKH assistance scheme because it will reduce the amount of assistance received by KPM and increase transportation costs. Besides that, it also has a big impact, especially for those whose assistance is of small value. The most important thing is that clear public communication and definite regulations are needed so that KPM is not confused by sudden changes in the scheme, and it is necessary to carry out synergies because the key to the success of this program lies in multi-stakeholder communication, cooperation, and coordination.